Low Molecular Weight Oligosaccharide from Panax ginseng C.A. Meyer against UV-Mediated Apoptosis and Inhibits Tyrosinase Activity In Vitro and In Vivo. (26th February 2021) - Dai, Yu-Lin; Yang, Di; Song, Lai-Hui; Yang, Hong-Mei; Yu, Jiang-Bo; Zheng, Fei; Yue, Hao; Chen, Chang-Bao; Wang, En-Peng
Abstract : To find new anti-UV and whitening agents, 21 fractions isolated from three preparations of ginseng (white, red, and black ginseng) were screened, and their antioxidant effects on AAPH- or H2 O2 -induced damage were investigated. Furthermore, the protective effect against UV-mediated apoptosis and the tyrosinase inhibitory activity of the targeted fractions were evaluated in vitro and in a zebrafish model. Among all fractions, F10 from white ginseng was selected as having the strongest anti-UV and antimelanogenesis activities. This fraction exhibited excellent inhibitory effects on the pigmentation of zebrafish, which may be due to its potential tyrosinase inhibitory activity. Additionally, the chemical composition of F10 was evaluated by UPLC-MS and NMR instruments. The results indicated that F10 had a carbohydrate content of more than 76%, and the weight-average molecular weight was approximately 239 Da. Disaccharide sucrose was the main active compound in F10. These results suggest that F10 could be used as an ingredient for whitening cosmetics and regarded as an anti-UV filter in the future.